NPM reconsidered : towards the study of enduring forms of NPM - Dan, Sorin; Lægreid, Per; Špaček, David (Taylor & Francis, 2024)
In this introduction to the special issue ‘The New Public Management: Dead or still alive and co-existing? State of play at 40+’ we suggest that we are witnessing two principal developments when it comes to NPM: its endurance in practice and reconsideration in theory. Building on recent research, we argue that NPM ideas and practices continue to be adopted, used, and tailored to meet reform requirements and preferences, resulting in enduring forms of NPM. Given its lasting influence on administrative practice, we propose the need for a reconsideration of the NPM paradigm within public administration scholarship. We conclude that NPM is a remarkable case of how management and governance ideas endure, leading to important implications for the conceptualization, research, and assessment of administrative movements and governance paradigms as they develop over time.
Keywords: Public sector reform; Public management; Public governance; New public management; Administrative movements; public administration; fi=Julkisjohtaminen|en=Public Management|